2016
DOI: 10.1016/j.biortech.2016.05.044
|View full text |Cite
|
Sign up to set email alerts
|

Development of a real-time bioprocess monitoring method for docosahexaenoic acid production by Schizochytrium sp.

Abstract: Oxygen uptake rate (OUR) and respiratory quotient (RQ) are key respiratory parameters for docosahexaenoic acid (DHA) production by Schizochytrium sp. HX-308 under dissolved oxygen limited conditions. To investigate the relationship of OUR and RQ with culture status, three independent cultures with different aeration rates were performed in a 50L bioreactor. OUR was found to be positively correlated with the aeration rate, which reflected the oxygen supply level in each culture. The highest biomass, reaching 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 34 publications
(27 reference statements)
0
17
0
Order By: Relevance
“…Thus, it was concluded that when RQ was controlled lower by feeding YE, the amino nitrogen concentration would be higher, thus the cell growth rate would be higher than the control. Guo et al ( 2016 ) also found that when RQ was controlled at 1.2 by enhancing the aeration rate to 1.5 VVM in DHA production by Schizochytrium sp., the biomass was the higher than the batches, which RQ was controlled at 1.7 or 2.0. So, RQ was a good online parameter to indicate the cell growth of oleaginous microbes.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Thus, it was concluded that when RQ was controlled lower by feeding YE, the amino nitrogen concentration would be higher, thus the cell growth rate would be higher than the control. Guo et al ( 2016 ) also found that when RQ was controlled at 1.2 by enhancing the aeration rate to 1.5 VVM in DHA production by Schizochytrium sp., the biomass was the higher than the batches, which RQ was controlled at 1.7 or 2.0. So, RQ was a good online parameter to indicate the cell growth of oleaginous microbes.…”
Section: Resultsmentioning
confidence: 96%
“…It was widely applied to optimization and scale-up in many fermentation processes, such as erythromycin and glutathione production (Xiong et al, 2010 ; Chen et al, 2015 ). Carbon source (Chen et al, 2015 ) and aeration rate (Guo et al, 2016 ) were the mainly studied factors in correlation with RQ. However, hardly any attention was paid on the relationship of RQ and the nitrogen feeding.…”
Section: Introductionmentioning
confidence: 99%
“…belongs to the Stramenopila (thraustochytrid) kingdom and generally lives in marine habitats throughout the world (Lippmeier et al, 2009;Fedorova-Dahms et al, 2011). Many studies have been concerned with cultivation optimization (Ling et al, 2015;Guo et al, 2016), safety evaluation of the algal oil (Lewis et al, 2016), and applications in the aquatic product industry (Ganuza et al, 2008;Li et al, 2009). To date, there have been only limited reports examining the antioxidant activity of these two microalgae.…”
Section: Introductionmentioning
confidence: 99%
“…A standard heterotrophic medium, MB10, was used as a starting point for the optimization of the culture medium. In the first trial, this basal medium was compared to MT1, a culture medium that was designed in accordance with the information available in the literature [2,6,10,11,14,17,20,[26][27][28][29][30][31][32][33][34]. The MT1 medium was tested using two trace metals solutions: (i) TM1, the trace metals solution of MB10; and (ii) TM2, formulated based on previous results obtained in the literature [6,8,10,14,16,17,20,24,26,27,[32][33][34][35].…”
Section: Effect Of Basal Culture Medium and Trace Metals Solutionmentioning
confidence: 99%
“…From a biotechnological point of view, two main features are responsible for the increasing interest in this family of microorganisms. They display high growth performance, reaching very high cell concentrations in a few days, and exhibit the striking ability to produce and accumulate docosahexaenoic acid (DHA) [4][5][6]. In contrast with the majority of microorganisms that produce saturated fatty acids (FA) as energy storage lipids, thraustochytrids synthesize long chain-polyunsaturated fatty acids (LC-PUFAs), like DHA, as energy storage, by an alternative pathway catalyzed by the polyketide synthase (PKS) enzymatic complex [5,7].…”
Section: Introductionmentioning
confidence: 99%